The Dimensions of Expatriates Acculturation in China: A Review - Fangling, Bi; Janee Ali, Anees (KnE Social Sciences, 2023)
Trade globalization pushes multinational corporations (MNCs) to conduct business in many geographic regions, and talent flow has emerged as one of the main avenues for building the competitive advantage of international organizations. The work performance of expatriates is crucial for MNCs, which will suffer significant financial losses due to the high failure rate of expatriates. Therefore, itis important to focus on determining what led to the abroad assignment failing and then improving the expatriate’s work performance. Drawing on Black’s theory of cross-cultural adjustment, this paper reviews past research on the impact of expatriate management practices on work performance with facets of cross-cultural adjustment as a mediating variable. This paper proposes a new dimension that affects the acculturation of expatriates in China, namely Guanxi, and introduces it into the research framework. This integration offers a more comprehensive framework for future research. Keywords: MNCs, work performance, expatriates, Guanxi, cross-cultural adjustment